2012
DOI: 10.1519/jsc.0b013e318231a659
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Nonlinear and Linear Periodized Resistance Training

Abstract: The aim of this study was to investigate the effects of nonlinear periodized (NLP) and linear periodized (LP) resistance training (RT) on muscle thickness (MT) and strength, measured by an ultrasound technique and 1 repetition maximum (1RM), respectively. Thirty untrained men were randomly assigned to 3 groups: NLP (n = 11, age: 30.2 ± 1.1 years, height: 173.6 ± 7.2 cm, weight: 79.5 ± 13.1 kg), LP (n = 10, age: 29.8 ± 1.9 years, height: 172.0 ± 6.8 cm, weight: 79.9 ± 10.6 kg), and control group (CG; n = 9, age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
1
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 21 publications
1
64
1
7
Order By: Relevance
“…Several studies also observed chronic differences regarding distinct methods of periodization (Simão et al, 2012;Bartolomei et al, 2014;de Lima et al, 2012;Painter et al, 2012). The previous investigations differ from our experiment mainly for the population and RE methodology applied.…”
Section: Discussioncontrasting
confidence: 77%
See 4 more Smart Citations
“…Several studies also observed chronic differences regarding distinct methods of periodization (Simão et al, 2012;Bartolomei et al, 2014;de Lima et al, 2012;Painter et al, 2012). The previous investigations differ from our experiment mainly for the population and RE methodology applied.…”
Section: Discussioncontrasting
confidence: 77%
“…Similarly to Simão et al (2012) and Painter et al (2012) we found increments (verified by ESs) in maximum strength (1-RM) regardless of the periodization method, even though the population was composed of well-trained individuals. Furthermore, we found changes in local muscle endurance and this adaptation may be due to the variations in load zone, volume and rest interval length.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations